Accounting for extortion. (July 2019) - Neu, Dean
Abstract: This study analyzes how accounting participates in the business of extortion. Using a combination of archival, interview and participant observation data, we consider the extortion activities of two criminal organizations—the Mara Salvatrucha and Barrio 18—that operate in the Northern Triangle countries of El Salvador, Guatemala and Honduras. Starting from the assumption that the repetitive extortion activities of street gangs require organizational devices that coordinate activities and facilitate decisionmaking, we examine how street gangs use accounting. We also analyze how business targets react to receiving extortion demands. The analysis illustrates that both street gangsters and their extortion targets have a pre-existing existential relationship to accounting that influences how street gangsters use accounting as well as how business targets respond.